2001
DOI: 10.1002/jnr.1166
|View full text |Cite
|
Sign up to set email alerts
|

Expression of estrogen receptor (ER)‐α and ‐β immunoreactivity in hippocampal cell cultures with special attention to GABAergic neurons

Abstract: This study investigated the expression patterns of estrogen receptor-alpha (ER alpha) and -beta (ER beta) in the cultured hippocampal cells of neonatal rats by combined application of cell culture and immunocytochemistry. The results revealed that the expression difference between ER alpha and ER beta seemed to be not obvious in the cultured hippocampal cells of neonatal rats. Moreover, immunoreactivity for either ER alpha or ER beta was observed to be localized in the majority of not only neurons but also ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 25 publications
(40 reference statements)
1
26
1
Order By: Relevance
“…Consistent with previous reports (Su et al, 2001; Prange-Kiel et al, 2003), we readily observed expression of ER␣ and ER␤ within the cytosol and nucleus of cultured hip- Figure 10. Proposed mechanism by which estradiol produces bidirectional effects on CREB phosphorylation.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous reports (Su et al, 2001; Prange-Kiel et al, 2003), we readily observed expression of ER␣ and ER␤ within the cytosol and nucleus of cultured hip- Figure 10. Proposed mechanism by which estradiol produces bidirectional effects on CREB phosphorylation.…”
Section: Discussionsupporting
confidence: 92%
“…To our surprise, the present highly sensitive RT-PCR study demonstrated that ERα transcripts existed, although in significantly lower degree than ERb, in the neonatal (at least 1 ~ 3-daysold rats) cerebellum and olfactory bulb. Even in the cerebral cortex known to contain both ER subtypes in adult rats [3], [9], ERα transcripts in neonate were much higher than in adult rats, which is similar to the change of ER expression in the hippocampus as revealed by Western blot analysis [4]. One possible explanation for this discrepancy is that there may exist obvious changes of ERα expression across the structural and functional development of these brain areas from neonatal to adult.…”
Section: Resultsmentioning
confidence: 63%
“…Little information is available concerning ER in neonate, as well as the differences of ER /ER expression patterns between the neonatal and adult brain. A previous work revealed that there existed changes of ER /ER expression patterns in hippocampus [4] between neonatal (1 ~ 3days) and adult (250 ~ 350g) rats. The present study was designed to compare the presence and relative expression level of ER and ER mRNA in the cerebral cortex, cerebellum, and olfactory bulb of neonatal (1 ~ 3days-old) rats with that of adult (250 ~ 350g) rats, by use of highly sensitive reverse transcription-polymerase chain reaction (RT-PCR) techniques.…”
Section: Introductionmentioning
confidence: 98%
“…Estrogen has been reported to alter GABA conduction (Majewska, 1992); induce synaptosomal GABA release (Fleischmann et al, 1990); increase GABA A antagonist binding affinity and site number (Juptner et al, 1991;Jussofie et al, 1995;Maggi and Perez, 1986;Perez et al, 1988;Schumacher et al, 1989); increase GABA transporter 1 mRNA (Herbison et al, 1995); increase a 2 and g 1 GABA a receptor subunit mRNAs (Herbison and Fenelon, 1995); and alter GAD mRNA levels (Davis et al, 1996;Grattan et al, 1996;McCarthy et al, 1995;Weiland, 1992). Previous reports indicate that estrogen receptors are expressed by hippocampal and hypothalamic GABA neurons (Su et al, 2001). The potency of estrogen on GABAergic signaling varies by brain region and is under investigation (McCarthy, 1995;Paul and Purdy, 1992;Smith, 1989).…”
Section: Introductionmentioning
confidence: 99%